Application and limitation of portable microchip capillary electrophoresis with capacitively coupled contactless conductivity detection (MCE-C4D) system on water coolant system - Tan, Sharon Shu Yi (2015)
As portable Microchip Capillary Electrophoresis with Capacitively Coupled Contactless Conductivity Detection (MCE-C4D) systems are relatively new and are gaining interest as a fast, convenient, low cost and accurate detection method, this technology aims to be applicable for any type of ions in any liquid medium. In this research, the application of MCE-C4D on water coolant systems was tested by identifying the presence of metal ions. The presence of metal ions in water coolant systems speeds up precipitation and prevents heat exchange in the water pipes, leading to severe corrosion if overlooked. Standard samples of NH4+, K+, Ca2+, Na+, Mg2+ and Li+ ions from their respective salts were tested and calibration curves of peak height against concentration showed linear relationships between peak height and concentration. Cross referencing to the standard sample results, Ca2+ ions were identified in the water coolant sample. Limitations of the fabrication of plastic microchips were also identified and discussed in this study. The microchannel was not long enough for the effective separation of the ions during the process, resulting in poorly separated peaks. There was also no form of pre-concentration for ions of a lower concentration (ppb range). This affected the limit of detection (LOD) as to how low a concentration can be detected by the portable system. Increasing the length of the microchannel by using a spiral microchannel would give the ions more time to separate from each other for a more acccurate detection. Pre-conentration can be possible by the use of an asymmetrical microchannel to increase the concentration of the ions just before detection or by incorporating the electro-membrane extraction (EME) technique to pre-concentrate the ions before injection. The present study can be extended to other applications such as the detection of bacteria or towards improving the portable system by introducing an automated injector for a more convenient detection method.